Impact of demand-side constraints on the usage rates of financial goods & services in Azerbaijan that mainly thwarts the financial inclusion process - Mammadli, Lala (ADA University, 2021)
The purpose of the research study is to lay the solid foundation for characterization the fundamental and built-in constituents of financial consumption, more specifically the usage rate of financial services & goods by households. To this date, researchers and scholars have done mass of descriptive studies and measures to deduce and infer the most reasonable and sensible set of ramifications regarding the hitches and constraints that transpires within the boundaries of delivery of financial services and products. Recalling from the definition of financial inclusion, usage of finance is not predicated on the supply of financial utilities per se, but the demand-side constraints which substantially impact the access and affordability process. Therefore, it is more than necessary to cull the roots of causes to identify “financial exclusion” quicksand and take proactive measures to handle overwhelming recurring events. Since the demand-side factors which include gender, age, education, occupation, income can be suggestive of shortcomings within the usage of financial utility, the examination process was based on regression of quantitative data which essentially trawled from 300 household to facilitate statistical analysis. In order to reinforce the statistical analysis, the research additionally called for the credible and accurate data from the responses of households which are fundamentally featured with “reasoning” concept that enables every single household to disclose his/her reluctance to the financial consumption. The core reason behind running regression analysis is to derive as heedful appraisal process as the former research studies. The outputs of regression analysis epitomize the fact that the usage rates of financial goods & services are heavily contingent on age, education, occupation, income factors. Strictly speaking, any deviation that occurs in these factors respectively conduces to positive or negative shift in the usage rates.
Keywords: Business; Financial consumption.; Financial services.; Financial consumption -- Azerbaijan.